Eficiência de uso e doses de nitrogênio em trigo sob diferentes arranjos espaciais de plantas - Trevizan, Diego Maciel (2017)
An alternative to minimize Nitrogen (N) losses, beyond use of more efficient wheat (Triticum aestivum L.) varieties on the use of this nutrient, is the identification of managements to intensify the use of N. For the varieties and climatic conditions of Brazil, there are few studies that have quantified how the spatial arrangement of plants affects the N-use efficiency. The objective of this study was to evaluate the effect of different spatial arrangements (combination between seeding rates and row spacing) on agronomic performance and utilization of the applied mineral nitrogen. The experiment was conducted in Pato Branco in the crops year 2014 and 2015, in a randomized block design, a factorial model, with three replications. Two wheat cultivars (CD 150 and Ametista) were submitted to four seeding densities (150, 300, 450 and 600 seeds m-2), two N doses (20 to 120 kg ha-1) and two row spacings (0.17 and 0.25 m). The highest grain yields were reached at the lowest line spacing and high nitrogen dose for cultivars and evaluated years. The densities, for maximum technical efficiency, of 400 seeds m-2 for the cultivar CD 150 and 425 seeds m-2 for the cultivar Ametista provides highest grain yield, for both cultivars and years evaluated. The N-use efficiency, N-uptake efficiency and N-utilization efficiency were higher in the conditions with lower level of N. In both spacings used, N-use efficiency was favored in the least spacing, as well as N-uptake efficiency. The results showed that the N content from the mineralization of organic matter should be used as a parameter for N application in the cover. Thus, avoiding excessive use of it and optimize both the grain yield as the N-use efficiency parameters.